OFR-122-77 Mine Grounding Systems: Evaluation Of Ground Beds And Ground-Bed Monitors And Evaluation Of Modular Ground-Wire Monitor - Wils L. Cooley (The National Institute for Occupational Safety and Health (NIOSH), 1977)
Several aspects of coal mine safety-ground system operation are studied. Evaluations of two sophisticated ground-wire monitors are presented, along with a detailed report of development work on a modular ground-wire monitor. A portion of the report covers stray current flow in the safety-ground system, analyzing in detail conditions surrounding the generation of both dc and ac ground wire current. Considerable detail is provided concerning studies of mine ground beds. Additional progress is reported in the development of a. continuous ground-bed monitor, and new techniques are developed for the design of ground beds and their resistance measurement. New methods of accurately measuring electrical parameters of finite layered conducting structures are also reported. The effects of stray currents in ground beds is included. Touch-and step-potentials associated with mining equipment are analyzed, and methods are presented for determining earth voltage gradients around structures contacting earth. Instrumentation to determine gradients easily is suggested. Finally, an extensive effort is described dealing with lightning transients on open-pit coal mine ground systems. The nature of the transients, their expected frequency of occurrence, and the ways in which they damage equipment are analyzed in detail.